2022
DOI: 10.1055/s-0042-1758366
|View full text |Cite
|
Sign up to set email alerts
|

Use of lacosamide in children: experience of a tertiary medical care center in Brazil

Abstract: Background Lacosamide (LCM) is a third-generation anti-seizure drug approved in Europe and the United States, either as a monotherapy or adjunctive therapy, to treat partial-onset seizures in adults, adolescents, and children. In Brazil, LCM is licensed for treatment only in patients older than 16 years of age. Objective To evaluate a cohort of children presenting with refractory epilepsy who received LCM as an add-on therapy and observe the response and tolerability to the LCM treatment. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…In 2022, Romão et al, 2022 conducted a retrospective cohort study in a tertiary healthcare facility in Brazil, which included 26 children with refractory epilepsy, and found the reduction of >50% in the frequency of seizures was 73.1% and 73.9% after 3 months and 9 months of LCM treatment, mild AEs were observed in very few children. In 2016, a large double-blind randomized controlled trial revealed that the average 4-week frequency of seizure episodes during the maintenance period with the use of 200 and 400 mg/day of LCM decreased by 29.4% and 39.6% in Chinese and Japanese adults, respectively, and the most common AEs were dizziness and drowsiness.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In 2022, Romão et al, 2022 conducted a retrospective cohort study in a tertiary healthcare facility in Brazil, which included 26 children with refractory epilepsy, and found the reduction of >50% in the frequency of seizures was 73.1% and 73.9% after 3 months and 9 months of LCM treatment, mild AEs were observed in very few children. In 2016, a large double-blind randomized controlled trial revealed that the average 4-week frequency of seizure episodes during the maintenance period with the use of 200 and 400 mg/day of LCM decreased by 29.4% and 39.6% in Chinese and Japanese adults, respectively, and the most common AEs were dizziness and drowsiness.…”
Section: Discussionmentioning
confidence: 99%
“…Compared with the previous studies, the responder rate for LCM and the percentage reduction in seizure frequency per 28 days were higher in our study, this may be because our subjects were not refractory epilepsy, and seizures were not very frequent (the number of seizure was less than 5 at baseline during 4 weeks) at the time of inclusion in the study. In addition, the above research included refractory epilepsy ( Feng et al, 2020 ; Romão et al, 2022 ), so the effect of drug control may be different in different types of epilepsy. In addition, the duration of the epilepsy time were 4.8 ± 3.4 and 4.49 ± 2.34, respectively ( Feng et al, 2020 ; Romão et al, 2022 ), which was longer than that in our study, so this may be also one of the reasons for the differences in effectiveness.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation